MONITOR [ENCICLOPEDIA] - Morera Ortiz, José (dirección) (SALVAT, 1972)
CONTENIDO: V. 1 A-ASTRA. -- V. 2 ASTRA-CALI. -- V. 3 CALM-CONS. -- V. 4 CONT-DRI. -- V. 5 DRO-FERO. -- V. 6 FER-GUAS.-- V. 7 GUAT-JAN. -- V. 8 JAPON-MERC. -- V. 9 MERE-PAQ. -- V. 10 PAR-RESP. -- V. 11 RES-TAN. -- V. 12 TAO-Z. -- V. 13.INDICE